Effect of physical therapy on bone remodelling in preterm infants: a multicenter randomized controlled clinical trial - Galaad Torró-Ferrero; Francisco Javier Fernández-Rego; María Rosario Jiménez-Liria; Juan Jose Agüera-Arenas; Jessica Piñero-Peñalver; María del Mar Sánchez-Joya; María Jesús Fernández-Berenguer; Mónica Rodríguez-Pérez; Antonia Gomez-Conesa (BMC Pediatrics, 2022)
Abstract Background Preterm infants have a low level of bone mineralization compared to those born at term, since 80% of calcium incorporation occurs at the end of pregnancy. The purpose of the present study was to investigate the effect of reflex locomotion therapy on bone modeling and growth in preterm infants and to compare its effect with those of other Physiotherapy modalities. Methods A multicentre randomized controlled clinical trial was conducted (02/2016 – 07/2020). 106 preterm infants born at the Virgen de la Arrixaca University Clinical Hospital, the General University Hospital of Elche and the Torrecárdenas University Hospital of Almería, between 26 and 34 weeks with hemodynamic stability, complete enteral nutrition and without any metabolic, congenital, genetic, neurological or respiratory disorders were evaluated for inclusion. Infants were randomly assigned to three groups: one group received reflex locomotion therapy (EGrlt); another group received passive mobilizations with gentle joint compression (EGpmc); and the control group received massage (CG). All treatments were carried out in the neonatal units lasting one month. The main outcome measure was bone formation and resorption measured with bone biomarkers. A mixed ANOVA was used to compare the results of bone biomarkers, and anthropometric measurements. Results Infants were randomized to EGrlt (n = 38), EGpmc (n = 32), and CG (n = 36). All groups were similar in terms of gender (p = 0.891 female 47.2%), gestational age (M = 30.753, SD = 1.878, p = 0.39) and birth weight (M = 1413.45, SD = 347.36, p = 0.157). At the end of the study, significant differences were found between the groups in their interaction in bone formation, measured with osteocalcin [F (2,35) = 4.92, p = 0.013, ηp 2 = 0.043], in benefit of the EGrlt. Conclusions Reflex locomotion therapy has been effective in improving bone formation, more so than other Physiotherapy modalities. Therefore, reflex locomotion therapy could be considered one of the most effective physiotherapeutic modalities for the prevention and treatment of osteopenia of prematurity. Trial registrstion Trial retrospectively registered at ClinicalTrials.gov. First posted on 22/04/2020. Registration number: NCT04356807 .